Annual report - International Finance Corporation (Washington, D.C International Finance Corporation (IFC), 1993)
Each issue consists of 2
Each report consists of 2 volumes Each issue has also a distinctive title
Keywords: International banking; FINANCE; DEVELOPING COUNTRIES; ANNUAL REPORTS; WORLD BANK